Mechanical stability of the CMS strip tracker measured with a laser alignment system. (21st April 2017) - Sirunyan, A.M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Friedl, M.; Frühwirth, R.; et al.
Abstract: The CMS tracker consists of 206 m 2 of silicon strip sensors assembled on carbon fibre composite structures and is designed for operation in the temperature range from −25 to +25° C. The mechanical stability of tracker components during physics operation was monitored with a few μm resolution using a dedicated laser alignment system as well as particle tracks from cosmic rays and hadron-hadron collisions. During the LHC operational period of 2011–2013 at stable temperatures, the components of the tracker were observed to experience relative movements of less than 30μm. In addition, temperature variations were found to cause displacements of tracker structures of about 2μm ° C, which largely revert to their initial positions when the temperature is restored to its original value.